Desenvolvimento e avaliação do potencial citotóxico de complexos de inclusão dronedarona/ciclodextrinas - Marcolino, Ana Isa Pedroso (2017)
Dronedarone is a new antiarrhythmic agent, analogue of amiodarone. Dronedarone was approved for the maintenance of the sinus rhythmic in adult patients with atrial fibrillation. Dronedarone show bioavailability problems due to its very low water solubility, slow dissolution rate and instability in the gastrointestinal tract. Cyclodextrins are cyclic oligosaccharides with a relatively hydrophobic central cavity and a hydrophilic surface. Because cyclodextrins can form complexes with a variety of organic molecules, they have been widely used to increase the solubility, stability and bioavailability of poorly soluble drugs. In the present study, complexes of dronedarone with β-cyclodextrin (β-CD) and 2-hydroxypropyl- β-cyclodextrin (HP-β-CD) were prepared with the aim to increase the aqueous solubility and dissolution properties of dronedarone. Solid inclusion compounds were obtained by mixing appropriate amounts of dronedarone and β-CD or HP-β-CD, in a 1:10 molar ratio. The preparation was carried out according to the lyophilization, co-lyophilization and kneading and spray-drying methods. Solubility studies were performed by phase solubility analysis. The complexes were characterized in the solid state by DSC, XRD, FTIR spectroscopy and SEM. Characterization of inclusion complexes by DSC and XRD showed that dronedarone appeared to exist in a non-crystalline form. The solubility of the complexes were evaluated and compared with pure drug. Dronedarone solubility was notably improved in simulated gastric fluid. The cytotoxicity of the inclusion complexes was evaluated by a simple method based on 3T3 embryonic mouse fibroblast monolayers culture using the reduction of 2,5-diphenyl-3,-(4,5-dimethyl-2-thiazolyl) tetrazolium bromide (MTT) as in vitro viability assay. The inclusion complexes with both cyclodextrins produced a significant reduction in cytotoxic effects compared with the free dronedarone. In order to determine the hepatotoxic potential of the free drug and inclusion complexes, the cytotoxicity was investigated using human hepatoma cell line HepG2. The assay results showed a dose response effect; higher drug concentrations induced a higher reduction in cell viability. No significant difference among the IC50 values of the free drug and inclusion complexes was observed, suggesting that inclusion complexation did not increase dronedarone hepatotoxic effect. The 3T3 Neutral Red Uptake phototoxic test was used to verify the phototoxic potential, while the in vitro photoassay using THP-1 human monocytes, with the interleukin 8 (IL-8) expression as endpoint, was used to determine the photosensitizing potential of free dronedarone and its inclusion complexes with β-CD or HP-β-CD. The free drug and inclusion complexes did not show photoirritant potential. In the photosensitizing assay, inclusion complexes prepared with β-CD by kneading following spray-drying induced lower photosensitization in comparison to free dronedarone. Finally, cyclodextrins were able to form inclusion complexes with dronedarone, and provided an improved solubility and chemical stability, reducing drug cytotoxic potential. Thus, inclusion complexes with cyclodextrins might be a promising alternative in the development of formulations with improved therapeutic efficacy.